Volume 6 Number 1 2010
DOI: 10.18057/ijasc.2010.6.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Partial Loading on the Behaviour of Pallet Rack Structures

Abstract: This paper presents the results of an investigation into the effects of partial loading on the behaviour of steel pallet racks. A six level, six bay, 3-dimensional pallet rack frame model was built using ABAQUS and a geometrically non-linear analysis conducted. Twelve different load combinations were analysed under different boundary conditions and different side imperfections. Most combinations failed by sway buckling. Depending upon the side imperfection and the base condition critical combinations involved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The results revealed that the distribution of load under partial load is frequently the cause of structural failure of the rack. Qarud et al [24] developed a six-level, six-bay, three-dimensional FE model of a steel storage rack using ABAQUS and performed multiple non-linear analyses on the steel storage rack under full or partial load. The study found that a steel storage rack under partial load is more dangerous than one under full load because only the steel storage rack under full load did not fail in the global sway mode.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results revealed that the distribution of load under partial load is frequently the cause of structural failure of the rack. Qarud et al [24] developed a six-level, six-bay, three-dimensional FE model of a steel storage rack using ABAQUS and performed multiple non-linear analyses on the steel storage rack under full or partial load. The study found that a steel storage rack under partial load is more dangerous than one under full load because only the steel storage rack under full load did not fail in the global sway mode.…”
Section: Introductionmentioning
confidence: 99%
“…The aforementioned studies revealed the potential risks of partially loaded racks. However, those experiments and numerical simulations [21][22][23][24][25] were limited and only reflected the relationship between several specific load distributions and the stability of steel storage racks. Investigating the relationship between load distribution and steel storage rack stability by increasing the number of test specimens or the number of finite element models requires significant financial or computational costs.…”
Section: Introductionmentioning
confidence: 99%